Growth and Yield Attributes of Groundnut (Arachis hypogea) as Influenced by Population Density and Phosphorous Fertilizer Rates on the Jos Plateau (Journal of Environmental Bioremediation and Toxicology, 2021)
The experiment was conducted at the Federal College of Forestry demonstration farm Jos, Plateau State, Nigeria. The experimental design used was a Randomized Complete Block Design (RCBD) consisting of twelve treatments combination arranged in 3 x 4 factorial (plant population density; 133,333 at 50 x15 cm, 100,000 at 50 x 20 cm and 80,000 plant/ha at 50 x 25 cm spacing and phosphorous; 0, 20, 40 and 60kgP2O5/ha) replicated four times. Data were collected on plant height, leaf count, canopy spread, stem girth, leaf area, leaf area index, number of pods/plant, 100 seeds weight, shelling percentage, pod yield, total biomass and harvest index. Data collected were subjected to analysis of variance (ANOVA) at a 5% level of significance. Duncan Multiple Range Test (DMRT) was used to compare the means. The result obtained reveals that a plant population density of 100,000 plants/ha and the application of 40 kg P2O5/ha produced the highest growth and yield characters of groundnut respectively. No significant influence of interaction was recorded on the growth and yield characters but significantly influence the yield of the groundnut plant. The interaction between population density of 100,000/ha and phosphorous fertilizer at 40 kg P2O5/ha gave the highest pod yield/ha (2.50 t/ha). It is therefore recommended that a plant population of 100,000 plants/ha and the application of 40 kg P2O5/ha be encouraged for farmers of groundnut in the study area for optimum production.
Keywords: density; phosphorous; fertilizer; groundnut; growth yield